1998
DOI: 10.1177/000348949810700611
|View full text |Cite
|
Sign up to set email alerts
|

Branchial Cleft Cyst Carcinoma: Myth or Reality?

Abstract: Skepticism has surrounded the existence of branchial cleft carcinoma since the entity was first described in 1882. However, a landmark work of 1950 established four criteria for the diagnosis of branchial cleft carcinoma, the most important criterion being histologic proof of carcinoma arising from a normal cyst epithelium. Of the 43 cases found in an extensive review of the literature, only 7 cases have satisfied all four of the criteria. To this we add 2 patients who had recurrent infections of a cervical cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
2

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 11 publications
0
26
0
2
Order By: Relevance
“…The controversy arises because 1) jugular lymphatics and most branchial cysts are found in similar locations, 2) metastatic squamous cell carcinoma is expected to occur with far greater frequency than branchial cleft carcinomas, 3) cervical metastases may be the first presentation of an occult lesion in the upper aerodigestive tract, and 4) histologically, it is difficult to distinguish branchial cleft carcinoma from cystic degeneration of a metastatic lymph node. 3,10 Although the histological appearance in this case is similar to that seen in a branchial cleft carcinoma, the presence of a known primary in the left‐side tonsil provides ample evidence against this diagnosis.…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…The controversy arises because 1) jugular lymphatics and most branchial cysts are found in similar locations, 2) metastatic squamous cell carcinoma is expected to occur with far greater frequency than branchial cleft carcinomas, 3) cervical metastases may be the first presentation of an occult lesion in the upper aerodigestive tract, and 4) histologically, it is difficult to distinguish branchial cleft carcinoma from cystic degeneration of a metastatic lymph node. 3,10 Although the histological appearance in this case is similar to that seen in a branchial cleft carcinoma, the presence of a known primary in the left‐side tonsil provides ample evidence against this diagnosis.…”
Section: Discussionmentioning
confidence: 70%
“…Gourin and Johnson 6 found no examples in their series of 121 patients, and Neel and Pemberton 11 found no such cases in 319 patients with lateral neck cysts. Furthermore, following extensive review of the literature, Singh et al 3 identified only 10 patients who met all the criteria for branchial cleft carcinoma set forth by Martin et al 2 Although it is possible that an epidermoid carcinoma may arise within a vestigium of the branchial apparatus, the diagnosis of a branchial cleft carcinoma should be questioned if the published criteria are not met. In these cases, a delay in proper diagnosis and treatment of an occult primary may lead to deleterious effects for the patient.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Extensive surgical excision and neck dissection are often recommended. Adjuvant radiation therapy is helpful in preventing a relapse, particularly for patients who receive limited resection, are unwilling to undergo further lymphatic dissection or have positive lymph nodes (5,13). The patient in the present case received a wide surgical excision of the lesion in addition to the dissection of the lymph nodes of the upper neck.…”
Section: A B C Dmentioning
confidence: 86%
“…Difernecijalno dijagnostički treba isključiti tuberkulozne čvorove, moguće primarne tumore tog sijela kao što su lipomi, neurinomi, kemodektomi i limfomi te moguće metastaze karcinoma u limfne čvorove. Također treba isključiti mogućnost postojanja branhiogenog karcinoma koji može nastati iz branhiogene ciste, kao i na postojanje cistične metastaze nekog drugog primarnog tumora [14][15][16][17][18][19][20][21] . U postavljanju dijagnoze uz anamnezu i klinički pregled u najvećem broju slučajeva radi se ultrazvuk vrata te citološka punkcija.…”
Section: Raspravaunclassified